The Framing of Speech Fluency in English as a Foreign Language (EFL) by In-Service Primary School Teachers - Kapranov, Oleksandr (Complutense Journal of English Studies, 2019)
The article presents a mixed-method study of how in-service primary school teachers frame speech fluency in English as a Foreign Language (EFL). In the present study, a group of 19 in-service primary school teachers (further - participants) are asked to write reflective essays on the topic “My Understanding of Speech Fluency in EFL”. The corpus of the participants’ reflective essays has been contrasted with the reflective essays written on the same topic by a control group, which is comprised of 19 EFL pre-service primary school teachers. The results of the framing analysis reveal that the participants frame speech fluency in EFL by the frames Communication, Disfluency, Flow, Grammar, Importance, Multimedia, Role Model, Vagueness, and Vocabulary. Notably, there are qualitative and quantitative differences in the distribution of the frames between the groups of participants and controls. The results of the data analysis indicate that the distribution of the frames involves such variables as the approach towards speech fluency in EFL and the participants’ view of their own speech fluency in EFL.